Analisis Sistem Informasi Akuntansi Pendapatan Penerimaan Kas Listrik Prabayar Pada PT Ajamu Faadhilah Agung - Liza Mutia; Arnida Wahyuni Lubis (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the accounting information system process regarding cash receipts from new prepaid electricity connections and meter replacement from postpaid to prepaid as implemented by PT. AJAMU FADHILAH AGUNG which is located at Pasar VII Street No. 2 Gg. Karya Rotan Sei Rotan Village. PT AJAMU FAADHILAH AGUNG is a company operating in the electrical and mechanical sector as a provider of electrical power installation services in Indonesia, so it is hoped that it can play an active role in supporting government policies together with PT. PLN (Persero). This research is limited to new connections to prepaid electricity and replacing meters from postpaid to prepaid. Problem formulation: 1. What is the accounting information system regarding cash receipts? 2. What are the advantages and disadvantages in implementing information systems. Research objectives: 1. To find out the application of accounting information systems regarding cash receipts. 2. To find out the advantages and disadvantages of applying accounting information systems regarding cash receipts. The data collection method used in this research is decision technique and direct research in the field. The technical analysis used is the description method, namely a method carried out by analyzing the cash receipts related to new prepaid electricity connections and meter replacement from postpaid - prepaid.